Host range functions of poxvirus proteins are mediated by species- specific inhibition of the antiviral protein kinase PKR - Haller, Sherry LaRae (Kansas State University, 2016)
Vaccinia virus is the prototypic poxvirus that has been widely used as a model for investigating poxvirus biology and genetics. Like several members of the Poxviridae family, vaccinia virus can infect several different species including mice, cows and humans. Because the entry of poxviruses into a host cell relies on ubiquitously expressed surface molecules, which are found in many species, the ability of poxviruses to infect and replicate in different host cells primarily depends on their ability to subvert the host’s innate immune response. One critical barrier to infection is overcoming the general shutdown of protein translation initiated by the cellular protein kinase PKR. PKR detects cytoplasmic double-stranded (ds) RNA generated during infection by the replicating virus, which activates it to phosphorylate the alpha-subunit of the eukaryotic translation initiation factor 2 (eIF2) and suppress general translation. Poxviruses are large viruses with dsDNA genomes that encode around 200 genes. Several of these genes are known as host range genes and are important for replication in different host species and many interact with components of the host immune response to promote viral replication. Two genes in vaccinia virus, called E3L and K3L, are known inhibitors of PKR and have previously been shown to be important for virus replication in cells from different species. The molecular explanation behind their host range function, however, is unknown. The main goal of the research presented in this thesis is to determine the molecular mechanisms for the host range function of vaccinia virus E3L and K3L, particularly in different hamster host cells. Along with an analysis of vaccinia virus host range genes, we have used genome-wide comparisons between host-restricted poxviruses in the Leporipoxvirus genus to parse out the potential genomic determinants of host range restriction in this clade of poxviruses. The overarching aim of this thesis work is to better understand the molecular mechanisms for host range in poxviruses.
Keywords: Innate immunology; Poxviruses; Host-virus interactions; Virus host range; Protein kinase R